2016
DOI: 10.1016/j.molcel.2016.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Memory Upgrade: Insights into Primed Adaptation by CRISPR-Cas Immune Systems

Abstract: Recently, Künne et al. (2016) demonstrated that degradation products of Cas3 obtained during CRISPR interference fuel priming. In this issue of Molecular Cell, Xue et al. (2016) highlight the conformational changes in Cascade that underpin the priming process when interference is blocked.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…From a strategic standpoint, once there is a sufficiently effective defense against common threats, it is more statistically effective to devote the remaining resources preferentially to rare threats. Indeed, although phenomena like priming can lead to acquisition of multiple spacers against a given virus (23)(24)(25)(26)(27)(28)(29)(30), several studies have shown that having just a few spacers from a given phage type is largely sufficient to neutralize reinfections (6,8,(16)(17)(18)(19). This means that the distribution of spacers should be more uniform than the distribution of pathogens-i.e., more weight should be given to rare infections than warranted by their frequency, again suggesting that a uniform distribution of spacers will be a reasonable approximation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From a strategic standpoint, once there is a sufficiently effective defense against common threats, it is more statistically effective to devote the remaining resources preferentially to rare threats. Indeed, although phenomena like priming can lead to acquisition of multiple spacers against a given virus (23)(24)(25)(26)(27)(28)(29)(30), several studies have shown that having just a few spacers from a given phage type is largely sufficient to neutralize reinfections (6,8,(16)(17)(18)(19). This means that the distribution of spacers should be more uniform than the distribution of pathogens-i.e., more weight should be given to rare infections than warranted by their frequency, again suggesting that a uniform distribution of spacers will be a reasonable approximation.…”
Section: Resultsmentioning
confidence: 99%
“…CRISPR cassettes can contain more than one spacer specific to a given virus. This can happen, for example, due to priming, where the presence of some spacers that at least partially match an invading phage can lead to acquisition of additional spacers (23)(24)(25)(26)(27)(28)(29)(30), increasing the effectiveness of the CRISPR-Cas system against recurrent or high-abundance viruses. On the other hand, having just a few spacers from a given phage type seems largely sufficient to neutralize reinfections (6,8,(16)(17)(18)(19), even from coevolving viruses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the scanning and recognition process of the open, and the L1 motif is exposed, which sparks primed adaptation from recruitment of Cas1:Cas2 and Cas3. Reused with permission from [144].…”
Section: Energy Efficiency and Stabilitymentioning
confidence: 99%
“…It was suggested that priming may explain the selection to retain old, imperfect spacers in the CRISPR locus, since they are still useful for priming from mutated or related invaders. Fluorescence resonance energy transfer (FRET) microscopy was used to demonstrate that the Cascade:targetDNA conformation depends on the presence of mutations in the PAM and seed regions, and this conformation dictates interference or primed adaptation activity [144]. As shown in figure 13, during target DNA binding, the large Cascade subunit Cas8e can either have a 'closed' or 'open' conformation, prompted by mutations in the protospacer PAM, protospacer seed, or a particular motif in Cas8e, 'L1'.…”
Section: Incomplete Target Recognitionmentioning
confidence: 99%